The U.S. Technology Frontier - Caselli, Francesco; Coleman, Wilbur John (American Economic Review, 2002)
In Caselli and Coleman (2000) we developed a framework that separately identifies the efficiency units embodied in unskilled labor, skilled labor, and capital in a country’s aggregate production function. Applying that framework to cross-country data, we showed that countries where unskilled labor is relatively abundant are those with the most efficient unskilled workers, while countries where skilled labor and capital are abundant are the most efficient users of these inputs. We interpreted these findings as evidence of appropriatetechnology adoption: in each country firms choose from a menu of technologies; different technologies imply different combinations of values for the efficiency units embodied in the three factors of production; in each country the technology is chosen that makes the most of the most abundant factors. In this paper we apply the same framework to time-series data from the United States over the period 1963–1992. We find that throughout this period the efficiencies of skilled labor and capital have risen. The efficiency of unskilled labor has risen in tandem with those of the other factors in the early part of the sample, but surprisingly, it has been falling since sometime in the 1970’s (the exact turning point depends somewhat on some parametric assumptions). In analogy with the cross-country evidence, these changes are closely associated with changes in the relative abundance of skilled labor and capital, which increased rather dramatically. In this sense, the recent history of technologies in use by U.S. firms may mimic the choice of technologies around the world today: as skills and capital become more abundant, technologies are chosen that maximize the efficiency of these inputs. As we discuss below, however, in the U.S. context the converse story (relative labor supplies adjusting to exogenous changes in technology) is also consistent with the data. Besides its relevance to models of technology adoption, this evidence also sheds new light on the widely documented recent increase in the skilled wage premium in the United States. Lawrence F. Katz and Kevin M. Murphy (1992) and David H. Autor et al. (1998) used the relative wage and the relative labor supply series to show that the efficiency of unskilled labor relative to skilled labor must have declined over time. Our framework allows us to go further and show that, indeed, the absolute efficiency of unskilled labor has fallen (after 1970), while the efficiency of skilled labor and capital have increased. A similar result was obtained with different techniques by Marta Ruiz Arranz (2001).